From subjective to objective requirements for conformity of goods in EU consumer law - Vujičić, Jovan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Unlike Directive 1999/44/EC which, in principle, had a subjective approach to determining the conformity of goods, Directive (EU) 2019/771 prescribes criteria that, as a rule, must always be met. In addition to reflecting the reasonable expectations of consumers, objective requirements for conformity also show what the legislator’s expectations are regarding the goods. In this sense, the concept of conformity has been significantly improved in the context of increased digitalization of goods. However, as far as sustainable consumption is concerned, the situation has largely remained unchanged, which is in contradiction with the existing policy of the European Union, as well as broader social and regulatory directions of development. The possibility of deviating from the objective requirements for conformity is reduced to the narrow framework of the exception, on the correct application of which depends whether it will fulfill its purpose.